2021
DOI: 10.1038/s41598-021-95248-4
|View full text |Cite
|
Sign up to set email alerts
|

Cottonseed-derived gossypol and ethanol extracts differentially regulate cell viability and VEGF gene expression in mouse macrophages

Abstract: Vascular endothelial growth factor (VEGF) plays an important role in chronic inflammation associated with several diseases. Many plant extracts have nutritional and healthy benefits by down-regulating VEGF expression, but there was no report on VEGF regulation by cottonseed extracts in any biological system. The objective was to investigate cell viability and VEGF expression regulated by gossypol and ethanol extracts using lipopolysaccharides (LPS) as a control. MTT, qPCR and immunoblotting techniques were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Idebenone metabolites (Benzenebutanoic acid and 2,5-dihydroxy-3,4-dimethoxy-6-methyl-) were previously reported in the methanolic and ethanolic extracts of Monotheca buxifolia [ 55 ] and from the butanolic fraction of Delphinium brunonianum together [ 56 ]. Gossypol, firstly isolated in 1889 from the seeds, roots, and stems of Gossypium members [ 57 , 58 ], was also reported in our study in the methanolic extract of T. musilii . Similarly, tripeptides and dipeptides were successfully identified by using the HR-LCMS technique in the organic extracts from T. polium [ 24 ], D. brunonianum [ 55 ], and A. subhirsutum [ 59 , 60 ].…”
Section: Discussionsupporting
confidence: 74%
“…Idebenone metabolites (Benzenebutanoic acid and 2,5-dihydroxy-3,4-dimethoxy-6-methyl-) were previously reported in the methanolic and ethanolic extracts of Monotheca buxifolia [ 55 ] and from the butanolic fraction of Delphinium brunonianum together [ 56 ]. Gossypol, firstly isolated in 1889 from the seeds, roots, and stems of Gossypium members [ 57 , 58 ], was also reported in our study in the methanolic extract of T. musilii . Similarly, tripeptides and dipeptides were successfully identified by using the HR-LCMS technique in the organic extracts from T. polium [ 24 ], D. brunonianum [ 55 ], and A. subhirsutum [ 59 , 60 ].…”
Section: Discussionsupporting
confidence: 74%
“…The results from this study and several previous studies suggest that gossypol is a strong stimulator of gene expression in mouse macrophages for the following reasons: (1) gossypol increases mRNA-destabilizing anti-inflammatory TTP family gene expression (TTP/ZFP36L1, ZFP36L2, ZFP36L2 and ZFP36L3) (this study); (2) gossypol increases proinflammatory cytokine gene expression (this study); (3) gossypol increases mRNA-stabilizing human antigen R (HuR) gene expression [ 52 ]; (4) gossypol increases vascular endothelial growth factor (VEGF) gene expression [ 53 ]; (5) gossypol increases glucose transporter gene expression (this study); (6) gossypol increases insulin signaling pathway gene expression (INSR, AKT1 and PIK3R1) (this study); (7) gossypol increases diacylglycerol acyltransferase (DGAT) gene expression [ 48 ]. However, since gossypol induced cell death at the same time, it is still to be determined if the gene expression effect was due to the direct or indirect effect of gossypol in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that gossypol induced macrophage death and reduced protein content that was accompanied with elevated levels of anti-inflammatory TTP family and proinflammatory cytokine gene expression as well as glucose transporter and insulin signaling pathway gene expression in mouse macrophages. We recently showed that gossypol strongly stimulated DGAT, HuR and VEGF gene expression in mouse macrophages [48,52,53]. Taking together, these studies indicate that gossypol derived from cottonseed may be a powerful stimulator of gene expression involved in inflammatory responses, glucose transport, insulin signaling and lipid biosynthesis in mouse macrophages, regardless its direct or indirect effects.…”
Section: Discussionmentioning
confidence: 84%
“…The results from this study and several previous studies suggest that gossypol is a strong stimulator of gene expression in mouse macrophages for the following reasons: 1) Gossypol increases mRNA destabilizing anti-inflammatory TTP family gene expression (TTP/ZFP36L1, ZFP36L2, ZFP36L2 and ZFP36L3) (this study); 2) Gossypol increases proinflammatory cytokine gene expression (this study); 3) Gossypol increases mRNA stabilizing human antigen R (HuR) gene expression [52]; 4) Gossypol increases vascular endothelial growth factor (VEGF) gene expression [53]; 5) Gossypol increases glucose transporter gene expression (this study); 6) Gossypol increases insulin signaling pathway gene expression (INSR, AKT1 and PIK3R1) (this study); 7) Gossypol increases diacylglycerol acyltransferase (DGAT) gene expression [48]. However, since gossypol induced cell death at the same time, it is still to be determined if gene expression effect was due to direct or indirect effect of gossypol in the cells.…”
Section: Discussionmentioning
confidence: 95%